Current issues in morphological theory : (ir)regularity, analogy and frequency : selected papers from the 14th International Morphology Meeting, Budapest, 13-16 May 2010 - Kiefer, Ferenc; Ladányi, Mária; Siptár, Péter (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory ;, 2012)
The present volume contains selected papers from the 14th International Morphology Meeting held in Budapest, 13-16 May 2010, organized under the auspices of the Research Institute for Linguistics of the Hungarian Academy of Sciences. The selection of papers presented here addresses problems of language use in one or another sense, covering issues of regularity, irregularity and analogy, as well as the role of frequency in morphological complexity, morphological change and language acquisition. The languages discussed include Dutch, German, Greek, Hungarian, Lovari (Romani) and Russian. The con.